Body asymmetries as risk factors for musculoskeletal injuries in dancesport, hip-hop and ballet dancers? - Monika Pavlović; Nina Ogrinc; Nejc Šarabon (PAGEPress Publications, 2022)
Objectives: The study aimed to determine the incidence and expression of body asymmetries in dancers of three different dance styles: dancesport (n = 14), hip-hop (n = 21) and ballet (n = 20) and to examine how body asymmetries (muscle strength and power, stability and range of motion) are associated with musculoskeletal injuries occurring over the past 12 months. Design: Cross-sectional and retrospective study. Methods: Maximal isometric voluntary contraction was measured for trunk, hip, knee and ankle movements. Participants performed a single leg stance, unilateral landing, weight bearing symmetry, squat and countermovement jump on force platforms. Passive range of motion was measured for hip, knee and ankle with two-arm goniometer or digital inclinometer (hip flexion, extension and rotations). A retrospective questionnaire was used to collect data on musculoskeletal injuries occurring in the last 12 months. Results: Different dance styles were associated with different body asymmetries, including strength asymmetries (hip flexion and external rotation), agonist/antagonist asymmetries (trunk flexion/extension, hip abduction/adduction, ankle dorsi/plantar flexion) and hip adduction and internal rotation range of motion asymmetries. Moreover, strength asymmetries of hip flexion, adduction and abduction/adduction as well as stability asymmetries were associated with the total number of musculoskeletal injuries. Conclusions: The incidence of body asymmetries (> 10%) in dancesport, hip-hop and ballet dancers was confirmed, as well as the association of some asymmetries with self-reported injuries occurring over the last 12 months. The cause-effect relationship should be clarified by further studies.